Numerical modelling of the cyclic behavior of timber-framed structures. (15th June 2018) - Lukic, Relja; Poletti, Elisa; Rodrigues, Hugo; Vasconcelos, Graça
Highlights: Timber-frames are earthquake-resistant due to the dissipative capacity of the joints. Concentrating non-linearity at wall joins accurately represents wall behavior. Slender walls lead to decreasing initial stiffness and lateral strength. Abstract: The present paper presents a study on the applicability of numerical models in predicting the global response of timber-framed shear walls during earthquake events. Based on previous in-plane cyclic testing of traditional timber frames with and without masonry infill, numerical models were developed to describe the cyclic response of traditional timber frame walls including flexural behavior, pinching and strength degradation. The numerical models were developed in the finite element software OpenSees with calibrated springs representing nailed connectors found in traditional half lap joints. Based on the calibrated models a study was conducted on the timber frame wall with brick infill model by varying wall configuration and analysing cumulative energy dissipation and the effect of slenderness and load capacity with increasing drift. A good correspondence was obtained with the experimental data and future work will include the application of the model to whole buildings.